Additional salt bridges improve the thermostability of 1, 4-α-glucan branching enzyme. (30th June 2020) - Ban, Xiaofeng; Wu, Jing; Kaustubh, Bhalerao; Lahiri, Pratik; Dhoble, Abhishek S.; Gu, Zhengbiao; Li, Caiming; Cheng, Li; Hong, Yan; Tong, Yi; Li, Zhaofeng
Highlights: A survey of proteins structures led to an effective method for introducing local salt bridges into proteins. Introducing new two-residue salt bridges into an 1, 4-α-glucan branching enzyme enhanced its thermostability by up to 50%. Expanding the two-residue salt bridges into three-residue salt bridge networks further increased enzyme thermostability. Abstract: The 1, 4-α-glucan branching enzyme from Geobacillus thermoglucosidans STB02 (GtGBE, EC 2.4.1.18) does not possess the thermostability required by modified starch industry. To increase its thermostability, a rational design strategy was used to introduce additional salt bridges into GtGBE. The strategy involved in mutation of individual residues to form "local" two-residue salt bridges. Accordingly, five of local salt bridges (Q231R-D227, Q231K-D227, T339E-K335, T339D-K335, and I571D-R569 mutants) were separately introduced into GtGBE. The half-times of these mutants at 60 °C were 17% to 51% longer than that of wild-type. Subsequently, these two-residue salt bridges were extended to form salt bridge networks (Q231R/K-D227-D131H, T339D/E-K335-I291H, and I571D-R569-R617H mutants). Among these mutants, except I571D-R569-R617H, the half-times of Q231R/K-D227-D131H, T339D/E-K335-I291H mutants at 60 °C were 15%, 17%, 21% and 17% longer than those of the corresponding two-residue salt bridges, respectively. The results showed that design and introduction of salt bridges improves enzyme thermostability in GtGBE.